Health comparison between guinea pigs raised in uncontrolled and controlled environments - Fitria, Laksmindra; Wijayanti, Nastiti; Arisuryanti, Tuty; Salasia, Siti Isrina Oktavia (Veterinary World, 2022)
Background and Aim: Guinea pigs (GPs) (Cavia porcellus) are not only kept as pets but also widely used in biological and biomedical research. At present, GPs are also used as a species for animal-assisted therapy (AAT). Consequently, assessing their health status is vital to determining their quality of life, usability for research, and prevention of spread of potential zoonotic diseases to patients using them for AAT. GPs are mainly sourced from animal markets supplied by traditional farms, where environmental factors and sanitation are not properly controlled. This study aimed to compare health status between GPs raised in uncontrolled (conventional farm) and controlled (animal facility) environments. Materials and Methods: Sample animals were obtained from a local animal market and transported to an animal facility. After 1 week of acclimatization, the health status of the animals, including general health condition, body weight, body temperature, complete blood count, liver function (alanine aminotransferase and bilirubin), renal function (blood urea nitrogen and creatinine), and presence of ectoparasites and endoparasites, was assessed. Then, the animals were maintained in the animal facility following the standard procedure for laboratory animals. After 2 months, the animals' health status was re-examined, assessing the same parameters. Results: Based on the evaluated parameters, GPs raised in an uncontrolled environment were found to have poorer health status than those raised in a controlled environment. There were significant differences in almost all parameters between GPs raised in controlled and uncontrolled environments. We found that the populations of two ectoparasites, Gyropus ovalis and Gliricola porcelli, and one endoparasite, Eimeria caviae, decreased significantly following the movement of the animals from an uncontrolled to a controlled environment. Conclusion: GPs raised in an uncontrolled environment have poor health status. However, a controlled environment with better care management can improve the health status of GPs.